A Critique on the Article Describing "Pancreatic Mucinous Cystic Neoplasm Size Using CT Volumetry, Spherical and Ellipsoid Formulas: Validation Study" - Aswani, Yashant; Anandpara, Karan Manoj; Acharya, Shrikala (JOP. Journal of the Pancreas, 2015)
No abstract available. Image: Seth Gordhandas Sunderdas (GS) Medical College and King Edward Memorial (KEM) Hospital. Mumbai, Maharashtra, India